Agriculture evolution, sustainability and trends, focusing on Brazilian agribusiness: a review - Basso, Marcos Fernando; Neves, Marcos Fava; Grossi-de-Sa, Maria Fatima (Frontiers in Sustainable Food Systems, 2024)
The world's population is expected to grow by 30-35% over the next 60 years. Forecasts indicate that the world's population will reach almost 10 billion by 2050, with India and China as the most populous countries. As a result, the demand for global food production, particularly protein and dairy products, and their nutritional quality will need to increase by 50-75%. In addition to increasing food production, it is also necessary to consider and reduce the impact on the environment and ecosystem. On the one hand, the threat of climate change, the reduction of arable land for agricultural expansion, the economic impact of geopolitical conflicts, the human and animal health pandemics, the conjuncture of the domestic political environments, and the demand for new technologies are the main bottlenecks to increasing sustainable food production worldwide. In contrast, notable technological advances have been achieved in current agriculture through basic and advanced scientific research, development, innovation, and technology transfer to the agribusiness sector. Technological advances in various sectors will become increasingly important to increase food production and minimize environmental impacts. This review study briefly highlights the major technological advances in world agriculture that have contributed to the substantial increase in food production from the early days of extractive agriculture to high-performance agriculture.It then highlights the key breakthroughs, disruptive technologies, the impact of climate change on agriculture, and contributions from molecular sciences that are revolutionizing global agriculture, focusing on Brazilian agriculture, livestock, and agribusiness. Subsequently, the evolution of Brazilian agriculture is highlighted based on the market share of agricultural products and its relevance to the national GDP. Finally, the potential decision-making that could have a positive impact on the Brazilian agribusiness sector and that will affect the import and export of agribusiness products were addressed.Therefore, the importance of supporting the agribusiness sector to increase healthy food production with higher nutritional quality and with less impact on the environment and human life was highlighted.